Tectonics, Structure And Floor Plan Of Taneyan Lanjhang Traditional Houses In Modern Madura Residential Houses - Poernama, Jessica Aprilia; Andriani, Celline; Regina, Fransiska Maria; Hastorahmanto, Prabani Setio; Putra, Heristama; Trisyanti, Lucia Ina (Jurnal Koridor, 2025)
Traditional houses are an important cultural asset in society. The Taneyan Lanjhang traditional house, a traditional house located in a certain area, has been the object of research in this study. This research aims to examine the tectonic and structural aspects of the Taneyan Lanjhang traditional house, including the geological characteristics that influenced its construction. The research method used in this study involves field surveys, primary and secondary data collection, as well as 3D rendering and qualitative descriptive explanations. Primary data was obtained through direct observation of the Taneyan Lanjhang traditional house, while secondary data was obtained through a study of related literature. Research shows that the Taneyan Lanjhang traditional house is supported by tectonic structures typical of the area. This structure plays an important role in the strength and stability of the traditional house. Some of the structural elements found include wooden columns, types of connections, and roof shapes.